How Family-Work Conflict Influences Post-traumatic Growth Among Medical Workers: A Moderated Mediation Model - Lv, Miao; Tan, Xuyun; Xing, Cai; Zheng, Jiaren; Han, Sixuan (Frontiers in Psychology, 2021)
Under the impact of COVID-19, the status and mechanisms of post-traumatic growth among medical workers facing challenges related to family-work conflict are of great concern. In view of the complex relationship between family-work conflict and post-traumatic growth, the present study sought to explore the specific relationships between family-work conflict and post-traumatic growth as well as the specific roles of positive psychological capital, perceived social support, and suppression. We recruited 1,347 participants. The results revealed that positive psychological capital and perceived social support played mediating roles, while suppression strategies moderated the mediating effect. Compared with the low suppression group, the negative impact of family-work conflict on positive psychological capital and perceived social support was reduced in the high suppression group. Thus, a higher level of suppression was more conducive to post-traumatic growth. The current study enriches and expands the findings of previous studies in theory and provides practical ways to promote post-traumatic growth in medical workers.